The Effect Of Social Media Marketing Activity And Brand Awareness On Purchase Intension With Brand Trust As A Mediating Variable On The Twitter Social Media Platform - Andy Agung Agnanto; Kurniawati Kurniawati (UNIVED Press, 2025)
Twitter is one example of a social media marketing strategy that companies may use to promote their brand online. From a variety of angles, earlier studies examined how various social media platforms influenced consumers' spending habits. With brand trust serving as a moderating variable, this research aims to examine the impact of social media marketing activity, brand awareness, and Twitter on purchase intention. It is crucial to use social media marketing to increase confidence in the company, which in turn increases the likelihood that consumers will make a purchase. Respondents in this study were users of the Twitter social media platform selected using non-probability sampling method. Using a Likert scale questionnaire instrument, this study employs a quantitative technique approach. Online, using Google Form, the survey was disseminated. The data analysis technique was carried out with the SPSS program by testing the validity, reliability and hypothesis on the questionnaire results obtained.